Mengenal Arsitektur Jengki : Warisan yang Nyaris Terlupakan - syifa, bilqis syifaur (Maliki Interdisciplinary Journal, 2025)
Jengki architecture developed in Indonesia during the 1950s to 1960s as an expression of independence and national identity. This style emerged as a reaction against Dutch colonial architecture, characterized by slanted roofs, asymmetrical facades, and unique geometric forms. As part of Indonesia’s early modernism, Jengki architecture reflects innovation and adaptation to the tropical environment. However, over time, many Jengki buildings have been renovated beyond recognition or demolished. This article explores the history, characteristics, and the urgency of preserving Jengki architecture as part of Indonesia’s cultural heritage. Through literature reviews from various sources, including journals, this study examines how conservation efforts can sustain its historical and aesthetic value. The findings suggest that Jengki architecture holds significant potential for conservation and cultural tourism. Preservation efforts should include documentation, education, and restoration of historic buildings. Public awareness and government support are essential to ensure this heritage is not lost due to urban development. Thus, preserving Jengki architecture not only safeguards cultural heritage but also strengthens Indonesia’s architectural identity.